Identifying children with anxiety disorders using brief versions of the Spence Children's Anxiety Scale for children, parents, and teachers - Reardon, T; Spence, SH; Hesse, J; Shakir, A; Creswell, C (American Psychological Association, 2018)
Anxiety disorders are among the most prevalent mental health disorders experienced by children and are associated with significant negative outcomes. Only a minority of affected children, however, access professional help, and a failure to identify children with anxiety disorders presents a key barrier to treatment access. Existing child anxiety questionnaire measures are long and time consuming to complete, limiting their potential for widespread use as identification tools in community settings. We developed a brief questionnaire for parents, children, and teachers using items from the Spence Children’s Anxiety Scale (SCAS) and evaluated the new measure’s psychometric properties, capacity to discriminate between a community (n 361) and clinic-referred sample (n 338) of children aged 7–11, and identified optimal cut-off scores for accurate identification of preadolescent children experiencing clinically significant levels of anxiety. The findings provided support for the reliability and validity of 8-item versions of the SCAS, with the brief questionnaire scores displaying comparable internal consistency, agreement among reporters, and convergent/divergent validity to the full-length SCAS scores. The brief SCAS scores also discriminated between the community and clinic-referred samples and identified children in the clinic-referred sample with a moderate-to-good level of accuracy and acceptable sensitivity and specificity. Combining reporters improved sensitivity, but at the expense of specificity, and findings suggested parent report should be prioritized. This new brief questionnaire has potential for use in community settings as a tool to improve identification of children who are experiencing clinically significant levels of anxiety and warrant further assessment and potential support.